1999
DOI: 10.1080/146392399298465
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the teleradiology technology (N-ISDN and ATM) on the inter-hospital management of neurosurgical patients

Abstract: We set out to assess the influence of a teleradiology network on the relations between a general hospital and a 100 km distant university hospital in the context of neurosurgical emergencies, and compared a commercially available technology, N-ISDN (Narrowband Integrated Service/Digital Network), to an emerging technology, ATM (Asynchronous Transfer Mode). The evaluation was conducted using records of advice request calls and patient transfers. Three phases were considered: without teleradiology, with transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…There are two approaches [4]: the first is known as "Application or Screen Sharing" [5,6,7,8,9,10,11] to whom also the Shared Whiteboard belongs; and the other is the socalled Command Passing or also "event/control sharing" [4,12,13,14,15,16,17,18,19,20]. There are two approaches [4]: the first is known as "Application or Screen Sharing" [5,6,7,8,9,10,11] to whom also the Shared Whiteboard belongs; and the other is the socalled Command Passing or also "event/control sharing" [4,12,13,14,15,16,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There are two approaches [4]: the first is known as "Application or Screen Sharing" [5,6,7,8,9,10,11] to whom also the Shared Whiteboard belongs; and the other is the socalled Command Passing or also "event/control sharing" [4,12,13,14,15,16,17,18,19,20]. There are two approaches [4]: the first is known as "Application or Screen Sharing" [5,6,7,8,9,10,11] to whom also the Shared Whiteboard belongs; and the other is the socalled Command Passing or also "event/control sharing" [4,12,13,14,15,16,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of publications that discuss in depth, the advantages and disadvantages of different methods of data transfer and maintaining cost effectiveness without compromising quality. [57][58][59][60][61][62] Stroke Stroke is a common clinical problem. Rapid treatment is crucial for effective intervention in acute ischemic stroke.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…129 New communication systems using international digital networks, including the internet, may allow re-distribution of medical resources between advanced countries and developing countries in neurosurgery. Telemedicine in neurosurgery between Japan and Malaysia using international digital telephone services has been accomplished.…”
Section: Other Issuesmentioning
confidence: 99%
“…Medicine has adopted this simpler form of teleradiology for distant and overseas hospitals and clinics. [2][3][4][5][6][7][8] Although there are conflicting reports on the effect of camera-digitization on image quality and radiographic interpretation, some studies have found that subtle lesions such as small nodules, small fractures, and pneumothoraces may be missed, although most have found no loss in interpretive accuracy. 3,[5][6][7][8][9] Both image quality and expertise affect the accuracy of image interpretation.…”
Section: Introductionmentioning
confidence: 99%